Does Money Matter? The Effects of Cash Transfers on Child Health and Development in Rural Ecuador - Paxson, Christina; Schady, Norbert (World Bank, Washington, DC, 2012)
The authors examine how a government-run cash transfer program targeted to poor mothers in rural Ecuador influenced the health and development of their children. This program is of particular interest because, unlike other transfer programs that have been implemented recently in Latin America, receipt of the cash transfers was not conditioned on specific parental actions, such as taking children to health clinics or sending them to school. This feature of the program makes it possible to assess whether conditionality is necessary for programs to have beneficial effects on children. The authors use random assignment at the parish level to identify the program's effects. They find that the cash transfer program had positive effects on the physical, cognitive, and socioemotional development of children, and the treatment effects were substantially larger for the poorer children than for less poor children. Among the poorest children in the sample, those whose mothers were eligible for transfers had outcomes that were on average more than 20 percent of a standard deviation higher than those for comparable children in the control group. Treatment effects are somewhat larger for girls and for children with more highly-educated mothers. The authors examine three mechanisms-better nutrition, greater use of health care, and better parenting-through which the transfers might influence child development. The program appeared to improve children's nutrition and increased the chance they were treated for helminth infections. But children in the treatment group were not more likely to visit health clinics for growth monitoring, and the mental health and parenting of their mothers did not improve.